2021
DOI: 10.1093/mnras/stab741
|View full text |Cite
|
Sign up to set email alerts
|

L-GALAXIES 2020: The evolution of radial metallicity profiles and global metallicities in disc galaxies

Abstract: We present a modified version of the L-Galaxies 2020 semi-analytic model of galaxy evolution, which includes significantly increased direct metal enrichment of the circumgalactic medium (CGM) by supernovae (SNe). These more metal-rich outflows do not require increased mass-loading factors, in contrast to some other galaxy evolution models. This modified L-Galaxies 2020 model is able to simultaneously reproduce the gas-phase metallicity (Zg) and stellar metallicity (Z*) radial profiles observed in nearby disc g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 178 publications
11
31
0
Order By: Relevance
“…2). This trend is in agreement with previous works on the evolution of the metallicity gradients in individual galaxies, which reported large scatter and rapid variation of the gasphase metallicity gradients for higher redshift (see also Ma et al 2017b;Yates et al 2021). Here, our goal is to trace the evolution of ∇ (O/H) for individual galaxies along their merger trees, while keeping a statistical approach.…”
Section: Evolution Of the Metallicity Gradients Of Individual Galaxiessupporting
confidence: 89%
See 1 more Smart Citation
“…2). This trend is in agreement with previous works on the evolution of the metallicity gradients in individual galaxies, which reported large scatter and rapid variation of the gasphase metallicity gradients for higher redshift (see also Ma et al 2017b;Yates et al 2021). Here, our goal is to trace the evolution of ∇ (O/H) for individual galaxies along their merger trees, while keeping a statistical approach.…”
Section: Evolution Of the Metallicity Gradients Of Individual Galaxiessupporting
confidence: 89%
“…This contributes to enhance the chemical content in the ISM, modifying the metallicity gradient gradually towards a shallower one. Hence, when galaxies with different formation histories are combined together, the correlation is likely to be suppressed or weakened due to the large variety of evolutionary tracks (Tissera et al 2016b), even if it exists for individual galaxies (Ma et al 2017a;Yates et al 2021).…”
Section: Ssfr Dependence Of the Metallicity Gradientsmentioning
confidence: 99%
“…A more self-consistent (although still approximate) estimate of the dust mass produced by Type I SLSNe at high redshift can be obtained from cosmological galaxy evolution simulations. For example, the cosmic dust production rate density (DD) from SLSNe can be calculated from the L-Galaxies 2020 semi-analytic model (Henriques et al 2020;Yates et al 2021). We assume that (a) Type I SLSNe only form in galaxies with gas-phase metallicity ≤ 0.5 Z , (b) the initial mass function (IMF) is fixed over time and space, (c) SLSNe produce 10 times as much dust per event as CCSNe, and (d) the shape of the DD evolution from SNe follows that of the cosmic star formation rate density (SFRD).…”
Section: Discussionmentioning
confidence: 99%
“…When analysing the chemical evolution of galaxies in L-G 2020, Yates et al (2021a) found that the default version of the model, which allows 70 per cent of the material ejected by SNe to directly enrich the ambient ISM, returned stellar and ISM metallicities that were too high compared to the latest global and spatially-resolved observational data (e.g. Zahid et al 2017;Belfiore et al 2017;Yates et al 2020).…”
Section: Parameter Changesmentioning
confidence: 99%